Negative impact of gestational diabetes mellitus on progress of pelvic floor muscle electromyography activity: Cohort study - Prudencio, Caroline B. [UNESP]; Rudge, Marilza V.C. [UNESP]; Pinheiro, Fabiane A. [UNESP]; Sartorão Filho, Carlos I. [UNESP]; Nunes, Sthefanie K. [UNESP]; Pedroni, Cristiane R. [UNESP]; Junginger, Baerbel; Barbosa, Angélica M.P. [UNESP] (Public Library of Science (PLoS), 2019)
Background and objective Pelvic floor muscles are involved in postural stability, in maintenance intra-abdominal pressure, and on mechanical support for pelvic organ. Gestational Diabetes Mellitus’ (GDM) pregnancies complicated by fetal macrosomia, large placenta and polyhydramnios contribute for abrupt and intense increase in maternal intra-abdominal pressure. Our objective was analyze the impact of GDM on pelvic floor muscle (PFM) electromyography (EMG) activity progress from 24–30 to 36–38 weeks of gestation. We conducted a prospective cohort study. PFM EMG was performed in nulliparous or primiparous women with one previous elective cesarean delivery and with or not GDM diagnosed by the American Diabetes Association criteria. A careful explanation of the muscle anatomy and functionality of the PFM was given before EMG assessment. The outcome measures were PFM recruitment and progress from 24–30 to 36–38 weeks of gestation analyzed by the normalized root mean square (RMS) during rest-activity, fast and hold pelvic floor muscle contraction. Results Fifty-two pregnant women were assigned to 2 groups: the GDM (n = 26) and normoglycemic (NG) (n = 26). The demographic and obstetric data showed homogeneity between the groups. PFM activity progress was decreased in rest-activity (P = 0.042) and hold contraction (P = 0.044) at 36–38 weeks of gestation in the GDM group relative to that in the NG group. Conclusion GDM group showed a progressive decrease in EMG-PFM activity during rest-activity and hold contractions from 24–30 to 36–38 weeks of gestation.